This is the story of you - Kephart, Beth (San Francisco : Chronicle Books, 2016)
Seventeen-year-old Mira lives in a small island beach town off the coast of New Jersey year-round, and when a devastating superstorm strikes she will face the storm's wrath and the destruction it leaves behind alone.
"A Junior Library Guild selection"--Jacket flap.
Keywords: Hurricanes -- New Jersey -- Juvenile fiction; Islands -- New Jersey -- Juvenile fiction; Survival -- Juvenile fiction; New Jersey -- Juvenile fiction; Hurricanes -- Fiction; Islands -- Fiction; Survival -- Fiction; New Jersey -- Fiction; Hurricanes -- New Jersey -- Fiction; Hurricanes -- New Jersey -- Juvenile fiction; Survival -- Juvenile fiction; Survival -- Fiction; Islands -- New Jersey -- Fiction; Islands -- New Jersey -- Juvenile fiction; New Jersey -- Juvenile fiction; New Jersey -- Fiction; Dystopian fiction